Sistematización del procesos socio organizativo de la Asociación SumakKawsay desde el enfoque generacional y de género - García Sánchez, Ana Lucía (2014)
The systematized experience refers to the significant progress that Sumak Kawsay association has reached in relation to gender equality , participation of youth and rural empowerment in the community, family and individual context considering the social , economic and cultural spheres . For the presentation of the experience in the first chapter key concepts, which are the basis for the same systematization of experience presented in the second chapter and the lessons learned are discussed in the third chapter based are synthesized which synthesize the findings . The conceptual framework refers to gender and its evolution in the social sciences starting from the age of feminism , women and development and gender in development , which realizes how from the construction of knowledge in the social sciences contribute in establishing a society more equitable in which individual rights are respected groups of women , men and generational groups , breaking power relations and Minions